2020
DOI: 10.1111/jace.17002
|View full text |Cite
|
Sign up to set email alerts
|

High energy storage efficiency and thermal stability of A‐site‐deficient and 110‐textured BaTiO3–BiScO3 thin films

Abstract: The development of thin film dielectrics having both high energy density and energy conversion efficiency, as well as good thermal stability, is necessary for practical application in high‐temperature power electronics. In addition, there is a demand for the development of new Pb‐free high‐energy density dielectric materials due to environmental concerns. In this regard, thin films of weakly coupled relaxors based on solid solutions of BaTiO3–BiMeO3 have shown good promise, because they exhibit a remarkably la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(30 citation statements)
references
References 50 publications
5
25
0
Order By: Relevance
“…For comparison, an overview of dielectric properties in commercially available capacitors and selected lead‐free dielectric materials is provided in Table 2. The synthesis temperature ( T S ) of the AD method is at room temperature, much lower than that of solid‐state reaction for the fabrication of commercial X7R multilayer ceramic capacitors (MLCCs) and other BT‐based ceramic capacitors 55–65 . It should be mentioned here that annealing at 500°C is required for AD‐BT films.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For comparison, an overview of dielectric properties in commercially available capacitors and selected lead‐free dielectric materials is provided in Table 2. The synthesis temperature ( T S ) of the AD method is at room temperature, much lower than that of solid‐state reaction for the fabrication of commercial X7R multilayer ceramic capacitors (MLCCs) and other BT‐based ceramic capacitors 55–65 . It should be mentioned here that annealing at 500°C is required for AD‐BT films.…”
Section: Resultsmentioning
confidence: 99%
“…The synthesis temperature (T S ) of the AD method is at room temperature, much lower than that of solid-state reaction for the fabrication of commercial X7R multilayer ceramic capacitors (MLCCs) and other BT-based ceramic capacitors. [55][56][57][58][59][60][61][62][63][64][65] It should be mentioned here that annealing at 500 • C is required for AD-BT films. In addition, the annealed AD-BT films exhibit high energy storage density and efficiency mainly due to the high electrical breakdown strength (E BDS ) and slim-like polarization loop.…”
Section: Effects Of Thermal Treatmentmentioning
confidence: 99%
“…It shows that the Pt layer in both the samples has a (200) orientation, in accordance with X-ray diffraction results from our previous work. 14 However, the crystallinity of the film layer immediately adjacent to the Pt-electrode is markedly different for the two samples. We observed a defective layer at the film− electrode interface of the BSBT 510 °C sample, which has an amorphous structure and varied thicknesses from region to region along the entire interface (see Figure 1).…”
Section: Experimental Techniquesmentioning
confidence: 93%
“…41 For example, Funakubo et al demonstrated that independent of the other parameters (i.e., composition, film thickness, and Pt-orientation), the temperature-dependent growth rate (V) of PZT films follow the V 100 > V 110 > V 111 sequence. 42 Here, for the BSBT 510 °C sample, since the crystalline layer in the bulk film grows on top of the interfacial amorphous layer, the film exhibits a (100) growth texture, 14 which is dictated by the lower PD of the (100) planes.…”
Section: Experimental Techniquesmentioning
confidence: 99%
See 1 more Smart Citation